German Jews in Sweden: Dialectics of symbiosis and coexistence - Gerner, Kristian (Nordisk judaistik, 2018)
Review of Deutschsprachige Jüdische Migration nach Schweden 1774 bis 1945, edited by Olaf Glöckner and Helmut Müssener (2017).